Volume 6: Ceramics; Controls, Diagnostics and Instrumentation; Education; Manufacturing Materials and Metallurgy 2014
DOI: 10.1115/gt2014-25640
|View full text |Cite
|
Sign up to set email alerts
|

NETL Research Efforts on Development and Integration of Advanced Material Systems and Airfoil Cooling Configurations for Future Land-Based Gas Turbine Engines

Abstract: As future land-based gas turbine engines are being designed to operate with inlet temperatures exceeding 1300°C (2370°F), efforts at NETL have been focused on developing advanced materials systems that are integrated with novel airfoil cooling architectures. Recent achievements in the areas of low cost diffusion bond coat systems applied to single- and poly-crystalline nickel-based superalloys, as well as development of thin nickel-based oxide dispersion strengthened layers are presented in this paper. Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These temperatures are at or exceeding current material (melting temperature) limits which require higher heat removal using novel blade designs to allow a more significant cooling of the substrate. 1 While the state-of-the-art internal cooling techniques generally provide a cooling enhancement about two to three times higher than baseline configurations, they would be more effective in lowering the airfoil substrate temperature if the internal channel was located closer to the airfoil external surface. 1 Collective durability data and analyses suggest that such a near-surface arrangement can not only substantially reduce the required coolant flow rate, thus directly increasing turbine system efficiency, but also significantly lengthen component life.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These temperatures are at or exceeding current material (melting temperature) limits which require higher heat removal using novel blade designs to allow a more significant cooling of the substrate. 1 While the state-of-the-art internal cooling techniques generally provide a cooling enhancement about two to three times higher than baseline configurations, they would be more effective in lowering the airfoil substrate temperature if the internal channel was located closer to the airfoil external surface. 1 Collective durability data and analyses suggest that such a near-surface arrangement can not only substantially reduce the required coolant flow rate, thus directly increasing turbine system efficiency, but also significantly lengthen component life.…”
Section: Introductionmentioning
confidence: 99%
“…1, is designed to further enhance heat transfer by moving the internal gas passage channels closer to the airfoil surface, providing more coolant closer to the hot gas path surface, thereby increasing heat removal capability on the order of 50–70% over that of advanced internal cooling technologies. 1 If the cooling channels can be incorporated within the actual surface layer and even more uniformly distributed throughout, as in a micro-porous surface layer structure, the cooling will be even further enhanced.
1 Sample geometry of the NSEMC cooling concept with a porous surface layer in a general airfoil cross-section (adapted from Alvin et al .
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional efforts were also addressed to establish the basis for enhanced stiffness response with extended high temperature cyclic testing of MCB plus ball milled ODS alloy systems in comparison to current/previously developed HVOF ODS alloy coating [154] and thermal barrier coating (TBC) systems [120] as a possible means of implementing these MCB plus ball milled ODS alloys as a structural high temperature coating on turbine blades by implementing microchannel cooling system beneath or within the coating [155]. In a similar test condition of this study, TBC systems [120] showed spallation failure after 400 thermal cycles, whereas oxide scales on MCB plus ball milled ODS alloy specimens were very adherent to the metal matrix without any spallation up to longer thermal cycles, more than 700 cycles.…”
Section: Temperature Distribution In the Model And Substratementioning
confidence: 99%